2023
DOI: 10.1001/jamanetworkopen.2023.4989
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Death Associated With Reversion From Prediabetes to Normoglycemia and the Role of Modifiable Risk Factors

Abstract: ImportanceIndividuals with prediabetes have a higher risk of death than healthy individuals. However, previous findings have suggested that individuals with reversion from prediabetes to normoglycemia may not have a lower risk of death compared with individuals with persistent prediabetes.ObjectivesTo investigate the associations between changes in prediabetes status and risk of death and to elucidate the roles of modifiable risk factors in these associations.Design, Setting, and ParticipantsThis population-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Study limitations included our inability to capture progression to diabetes as an intermediary end point due to lack of intercurrent diabetes assessments prior to events. In a study of 45 782 Asian individuals with prediabetes, at any given level of PA, progression to diabetes was a leading predictor of mortality . As with the Da Qing study, more benefit in the prediabetes group may occur after longer follow-up .…”
Section: Discussionmentioning
confidence: 99%
“…Study limitations included our inability to capture progression to diabetes as an intermediary end point due to lack of intercurrent diabetes assessments prior to events. In a study of 45 782 Asian individuals with prediabetes, at any given level of PA, progression to diabetes was a leading predictor of mortality . As with the Da Qing study, more benefit in the prediabetes group may occur after longer follow-up .…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is of utmost important in prediabetics. A recent study showed that conversion of euglycemia along with physically activity was associated with a lower risk of death compared with persistent PD and physical inactivity[ 133 ]. Keeping these facts in mind, it is important to fully educate prediabetic kidney donors about physical activity prior to donation.…”
Section: Is Ckd the Only Concern Of Pd?mentioning
confidence: 99%
“…Even assuming that all the individuals who died had developed diabetes before doing so (highly unlikely), 64% of those still living would not have developed diabetes. Furthermore, a mean of one-third, with a wide range of 13–69% depending on the diagnostic criteria used to diagnose prediabetes and euglycemia, returned to normal glucose regulation over time [ 10 , 14 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…The presence of prediabetes did not affect the clinical outcomes of patients who experienced an acute coronary syndrome, such as acute pulmonary edema, length of hospital stay, 28-day readmission rates, recurrence or CVD mortality, compared to those with normal HbA1c levels [ 16 ]. In individuals with IGT, the risk of CVD mortality was the same whether they returned to normal glucose regulation or not [ 14 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%
See 1 more Smart Citation